Isoprenylated flavanone derivatives from Macaranga hosei King ex Hook.F. - Marliana, Eva (scholars research library, 2015)
Two isoprenylated flavanones, 4’-O-methyl-8-isoprenylnaringenin (1) and lonchocarpol A (2) have been isolated from the leaves of Macaranga hosei King ex Hook.f. The structure of both compounds have been elucidated based on its spectroscopic data, including UV, 1D and 2D NMR, and HREISMS spectra. Compounds 1–2 were evaluated for their radical scavenging against 2,2-diphenyl-1-picrylhydrazyl (DPPH), showing their IC50 were 1298.0 and 1115.7 µM, respectively.